The Effect of Non-condensable Gases Removal on Air Gap Membrane Distillation: Experimental and Simulation Studies - Alsaadi, Ahmad S. (2014)
In the kingdom of Saudi Arabia (KSA), the current seawater desalination technologies are completely relying on burning unsustainable crude oil as their main energy driver. Saudi authorities have realized that the KSA is not going to be protected from the future global energy crisis and have started to set up a plan to diversify its energy resources. Membrane Distillation (MD) has emerged as an attractive alternative desalination process. It combines advantages from both thermal and membrane-based technologies and holds the potential of being a cost-effective separation process that can utilize low-grade waste heat or renewable energy. MD has four different configurations; among them is Air Gap Membrane Distillation (AGMD) which is the second most commonly tested and the most commercially available pilot-plant design. AGMD has a stagnant thin layer of air between the membrane and the condensation surface. This layer introduces a mass transfer resistance that makes the process require a large membrane surface area if a large quantity of fresh water is desired. This dissertation reports on experimental and theoretical work conducted to enhance the AGMD flux by removing non-condensable gases from the module and replacing it with either vacuum, liquid water or porous materials. At first, a mathematical model for AGMD was developed and validated experimentally to create a baseline for improvements that could be achieved after the removal of non-condensable gases. The mathematical model was then modified to simulate the process under vacuum where it showed a flux enhancement that reached 286%. The Water Gap Membrane Distillation (WGMD) configuration improved the flux by almost the same percentage. Since enhancing the flux is expected to increase temperature polarization effects, a theoretical study was conducted on the effect of temperature polarization in a Vacuum Membrane Distillation (VMD) configuration. The study showed that the effect of temperature polarization at small temperature difference (3-7) degree Celsius between the bulk feed and coolant temperatures is significantly high. This may indicate the importance of mitigating the effect of temperature polarization in large scale modules operating at small temperature difference across the membrane. The dissertation concluded with some recommendations for future work.